2018
DOI: 10.1016/j.cell.2018.02.052
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated TCGA Pan-Cancer Clinical Data Resource to Drive High-Quality Survival Outcome Analytics

Abstract: Graphical Abstract Highlights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
2,243
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,625 publications
(2,268 citation statements)
references
References 49 publications
19
2,243
2
4
Order By: Relevance
“…TCGA bam files used in the analyses were downloaded from the Genomic Data Commons Data Portal (https://portal.gdc.cancer.gov). Clinical and survival data of TCGA samples were retrieved from Reference . Genetic variability data of ABC transporters in the general population were retrieved from the Genome Aggregation Database (http://gnomad.broadinstitute.org/).…”
Section: Methodsmentioning
confidence: 99%
“…TCGA bam files used in the analyses were downloaded from the Genomic Data Commons Data Portal (https://portal.gdc.cancer.gov). Clinical and survival data of TCGA samples were retrieved from Reference . Genetic variability data of ABC transporters in the general population were retrieved from the Genome Aggregation Database (http://gnomad.broadinstitute.org/).…”
Section: Methodsmentioning
confidence: 99%
“…For the first time, we assessed the expression of PP2A endogenous inhibitors (Table ) in two mesothelioma patient data sets: the Gordon data set from NCBI Gene Expression Omnibus database (Gordon et al, ), which contains five samples of normal pleura and 40 samples of mesothelioma tumor samples, and The Cancer Genome Atlas (TCGA) data set with 87 mesothelioma tumor samples (Liu et al, ). At first, we found that ARPP19, ANP32E, TIPRL, SET, PPME1, and ANP32A genes are all overexpressed in patient samples when compared to normal pleural tissue samples (Figures a and b).…”
Section: Resultsmentioning
confidence: 99%
“…(a) Expression of SET, ARPP19, ANP32E, TIPRL, (b) PPME1 and ANP32A in normal pleura and pleural mesothelioma samples from publicly available data set (GSE2549; Gordon et al, ). (c) Overexpression percentage (red portions) of ANP32E, CIP2A (KIAA1524), TIPRL, ANP32A, ARPP19, SET and PPME1 in pleural mesothelioma samples retrieved from cBIOportal (TCGA‐MESO phs000178, (Gao et al, ; Liu et al, ). (d) Overall survival Kaplan‐Meyer curve of concomitant ANP32E and CIP2A altered gene expression in The Cancer Genome Atlas (TCGA) mesothelioma patient data set…”
Section: Resultsmentioning
confidence: 99%
“…The clinical and follow‐up information of 134 TGCT samples were obtained from a previous TCGA study (Table ). As for the few disease‐specific survival and overall deaths of TGCT patients, we used disease‐free interval (DFI) and progression‐free interval (PFI) as clinical outcome endpoints .…”
Section: Methodsmentioning
confidence: 99%
“…The clinical and follow‐up information of 134 TGCT samples were obtained from a previous TCGA study (Table ). As for the few disease‐specific survival and overall deaths of TGCT patients, we used disease‐free interval (DFI) and progression‐free interval (PFI) as clinical outcome endpoints . We performed a multivariate Cox proportional hazards regression model to calculate the Hazard Ratio (HR), the 95% confidence interval (95% CI), and P ‐values with adjustments for age and tumor stage.…”
Section: Methodsmentioning
confidence: 99%